DAMPAK BENCANA BANJIR DAN PERSEPSI MASYARAKAT TERHADAP PROGRAM NORMALISASI SUNGAI BATANG SINAMAR DI NAGARI TARAM KECAMATAN HARAU KABUPATEN LIMAPULUH KOTA - Heri Faldi; Iswandi Umar (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The puposes of this research are (1) the impact of the flood on the people of Jorong Subarang and Jorong Tanjung Kubang in Nagari Taram (2) Perceptions of the people of Jorong Subarang and Jorong Tanjung Kubang in Nagari Taram. The type of research used is Mixed Methods. The data analysis technique used was a questionnaire based on the Likert scale and the Miles and Huberman data analysis model. The results of this study indicate that (1) The impact of floods on physical variables in the indicators of market damage is classified as very good, housing damage is classified as severe. The social variable is the contamination of clean water sources, the environmental variable is the damage to plants/plants, the environmental variable is the occurrence of water pollution from the river due to flood material, the economic variable is lost and damaged property, the economic variable is the inhibition of livelihoods, all of which are classified as severe. (2) Community perceptions of the program river normalization, indicators of counseling on river normalization, residents understand the results of counseling, have a positive impact on society, make rivers better at flowing water downstream of rivers, minimize flooding, make river water flow not overflow into residential areas, make river cliffs to be solid, the loss of the costs of cleaning and repairing the house are all classified as right and damage the economy of the citizens are classified as doubtful. Keywords : Flood Impact, River Normalization, Community Perception